The English cathedral - Peter Marlow; Barnes, Martin, 1971-; Goodall, John A. A. (London Merrell, 2015)
Among the most magnificent buildings of England are its Anglican cathedrals, great symbols of spiritual and architectural power. No one can fail to marvel at Durham's incomparable Romanesque masterpiece, the elegant stylistic unity of Salisbury, the world-famous stained glass of Canterbury or the striking Gothic scissor arch at Wells. In this breathtaking new book, award-winning Magnum photographer Peter Marlow has captured the nave of each of England's 42 Anglican cathedrals. Taken in natural light at dawn, usually looking towards the east end of the building, these remarkable images bring into sharp relief the full splendour of the architecture, whatever the style. Marlow's spellbinding photographs are accompanied by his commentary on the project, including sketches and preparatory shots; an introduction by curator Martin Barnes on the tradition of church photography in England, particularly the work of Frederick Evans and Edwin Smith; and a concise summary of each cathedral interior by architectural historian John Goodall.
Keywords: Christian Antiquities (3GdBKGQ GdeSjMjIs; History -- Cathedrals -- England -- Pictorial works; Anglican church buildings -- England -- Pictorial works; Anglican church buildings; Cathedrals